Correction: Cognitive Test Scores in UK Biobank: Data Reduction in 480,416 Participants and Longitudinal Stability in 20,346 Participants. - Donald M Lyall; Breda Cullen; Mike Allerhand; Daniel J Smith; Daniel Mackay; Jonathan Evans; Jana Anderson; Chloe Fawns-Ritchie; Andrew M McIntosh; Ian J Deary; Jill P Pell (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0154222.].